Spatial and numerical abilities as correlates of academic achievement in economics (2023)
The school system's primary concern and essential function are improving students' academic performance and producing a pool of skilled human resources to help grow and develop a nation. Despite how vital economics is to society, several factors determine students' choices and interests, among which spatial and numerical abilities are significant. This has led to students‟ inability to cope with real-life situations, self-independent, and basic entrepreneurial skills. The paper examined spatial and numerical abilities as correlates of academic achievement in Economics. Four research questions guided the study with three instruments to collect data analyzed using mean, standard deviation, and regression analysis at a 0.05 significance level. The results revealed that the mean of all items is higher than the criterion mean of 0.50. Students had a high level of spatial ability (0.50 < 0.91), but performance in numerical ability was poor (0.50 > 0.43). The relationship between the independent variable revealed a significant positive relationship (r= 0.17, p<0.05(0.00)). There was a significant effect of independent variables on the dependent variable (F(2,997)= 41.093; p<0.05(0.000)). Teachers should be trained on how to incorporate spatial ability in economics classes